Study of incidence, manifestations and complications of dengue fever - K., Jahnavi; T., Srinivasulu (International Journal of Advances in Medicine, 2018)
Background: Dengue is endemic in India and epidemics are common. Due to poor availability of resources, there is increased morbidity and mortality related to dengue. The objective of the research to study the incidence, manifestations and complications of dengue fever. Methods: Patients admitted in medicine wards of a tertiary care hospital during the study period of two years with the history of fever with other nonspecific symptoms were included in the present study. Data was collected in a pre-tested proforma by meeting objectives of the present study. 100 patients who fulfilled World Health Organization criteria for dengue fever were selected by simple random sampling method. Results: In 75 patients the platelet count was above 150000cell/cumm. Most of them had dengue fever. 12 patients showed platelet count between 20000-100000cells/cumm. and among them 10 were DHF and 2 were simple dengue infection. Five patients showed platelet count less than 20000cells/cumm. and among them 2 were DHF and 3 were DSS. Most of the bleeding skin manifestations were seen when platelet count was below 50000cells/cumm. Mucosal bleeding was observed when the platelet count was below 30000cells/cumm. Abnormal coagulation profile was noted in 18% of the patients and 6% patients were in acute renal failure. Mortality was 0% in dengue fever, 44% in DHF and 100% in DSS. Conclusions: Platelet count was directly related to the number of complications. Dengue shock syndrome and dengue hemorrhagic fever was associated with increased mortality.